(untitled) (Research Announcements "Heritage BG", 2025)
The epigraphical material from Apollonia Pontica provides a valuable opportunity to analyze the presence and acculturation of non-Greek individuals in the Milesian colony during the relatively early period of the 5th century BC. How do we measure the extent to which they are others? By scrutinizing and comparing the archaeological, epigraphic, and onomastic evidence about Greeks and non-Greeks in the colony with those of other cities in the Aegean area in the Classical Period, the paper provides a plausible reconstruction of the colonization process and the social structure of the town and also tries to define the methodological principles that should be applied in research of this kind. References: Adiego, I. J. (2007). The Carian Language. Leiden, Boston: Brill. Adiego, I. J. (2007a). Greek and Carian. In: A History of Ancient Greek: From the Beginnings to Late Antiquity (eds. A.-P. Christidis, M. Arapopoulou, M. Chriti). Cambridge University Press. Bäbler, B. (1998). Fleissige Thrakerinnen und wehrhafte Skythen. Nichtgriechen im klassischen Athen und ihre archäologische Hinterlassenschaft. Beiträge zur Altertumskunde, B. 108. Stuttgart und Leipzig: Teubner. Biering, R., Brinkmann, V., Schlotzhauer, U., Weber, B. F. (eds.) (2006). Maiandros. Festschrift für Volkmar von Graeve. München. Blümel, W. (1992). Einheimische Personennamen in Karien. - Epigraphica Anatolica, No. 20, 7-33. Brun, P. (ed.) (2007). Scripta Anatolica. Hommages Pierre Debord. Bordeaux. Brun, P. (2022). L’hellénisation passe-t-elle par le nom ? L’exemple de la Carie aux IVe et IIIe siècles av. J.-C. – Ktèma, no 47: D. Lenfant (ed.). Grecs et non-Grecs de l’empire perse au monde hellénistique, 175-204. Chu, J. J. (2022). Thracians Among Others. A Study of ‘Thracianness’ in Ancient Cross-Cultural Contexts. PhD Dissertation. UC Riverside Electronic Theses and Dissertations. https://escholarship.org/uc/item/55x5d5m3 Cohen, B. (ed.) (2000). Not the Classical Ideal: Athens and the Construction of the Other in Greek Art. Leiden, Boston: Brill. Crielaard, J. P. (2009). The Ionian in the Archaic Period: Shifting identities in a changing world. In: Ethnic Constructs in Antiquity. The Role of Power and Tradition (eds. A. M. J. Derks, N. G. A. M. Roymans). Archaeological Studies 13. Amsterdam University Press, 37-84. DeVries, K. (2000). The Nearly Other: The Attic Vision of Phrygians and Lydians. In: Not the Classical Ideal: Athens and the Construction of the Other in Greek Art (ed. B. Cohen). Leiden, Boston: Brill, 338-363. https://archive.org/details/notclassicalidea0000unse Detschew, D. (1976). Die thrakischen Sprachreste. Wien: Österreichische Akademie der Wissenschaften. Ehrhardt, N. (2005). Die Ionier und ihr Verhältnis zu den Phrygern und Lydern. Analyse der literarischen, epigraphischen und numismatischen Zeugnisse. In: Neue Forschungen zu Ionien. Fahri Içik zum 60. Geburtstag gewidmet (eds. E. Schwertheim, E. Winter). Asia Minor Studien 54. Bonn: Rudolf Habelt, 93-112. Ehrhardt, N. (2006). Die karische Bevölkerung Milets. In: Maiandros. Festschrift Volkmar von Graeve (eds. R. Biering). Biering & Brinkmann, 81-89. Ehrhardt, N. (2013). Archaische Vasengraffiti aus dem milesischen Aphrodite-Heiligtum in Oiskus. – In: Petasos. Festschrift für Hans Lohmann (eds. G. Kalaitzoglou, G. Lüdorf). Paderborn: Verlag Ferdinand Schöningh, 119-127. FD III: Fouilles de Delphes, III. Épigraphie. Paris, 1929–. Fraser, P. M. (2000). Ethnics as Personal Names. In: Greek Personal Names: Their Value as Evidence (eds. E. Matthews, S. Hornblower, P. M. Fraser). Proceedings of the British Academy, 104. Oxford: Oxford University Press, 149-157. https://archive.org/details/greekpersonalnam0000unse/page/n7/mode/2up Giuzelev, M. (2002). Ancient Funerary Monuments at Sozopol Archaeological Museum. - Bulletin du Musée National de Bourgas, No. 4, 119-129. Günther, W. (2017). Inschriften von Milet. Band VI. Teil 4. Eine Prosopographie. Berlin-Boston: De Gruyter. https://archive.org/details/mileteineprosopo0000wolf/page/594/mode/2up Herda, A. (2013). Greek (and our) View on the Karians. In: Luwian Identities. Culture, Language and Religion Between Anatolia and the Aegean (eds. A. Mouton, I. Rutherford, I. Yakubovich). Leiden, Boston: Brill, 421-506. Herda, A., Sauter, E. (2009). Karerinnen und Karer in Milet: Zu einem spätklassischen Schüsselchen mit karischem Graffito aus Milet. – Archäologischer Anzeiger, No.2, 51-112. https://publications.dainst.org/journals/aa/54/4731 I Aeg. Thrace: Epigraphes tes Thrakes tou Aigaiou: metaxy tôn potamön Nestou kai Hevrou (nomoi Xanthes, Rhodopes kai Hevrou) (eds. L. D. Loukopoulou, M. G. Parissaki, S. Psoma, A. Zournatzi) (2005). Athens. I Eleusis: Clinton, K. (2005-2008). Eleusis. The Inscriptions on Stone. Documents of the Sanctuary of the Two Goddesses and Public Documents of the Deme. 2 vols. in 3 parts. Vivliotheke tes en Athenais Archaiologikes Hetaireias, 236 and 259. Athens. IG I3: Inscriptiones Graecae I: Inscriptiones Atticae Euclidis anno anteriores. 3rd edn. Berlin 1981, 1994. IG II2: Inscriptiones Graecae II et III: Inscriptiones Atticae Euclidis anno posteriores, 2nd edn., Parts I–III (ed. J. Kirchner). Berlin, 1913-1940. IG V.2: Inscriptiones Graecae, V.2. Inscriptiones Arcadiae (ed. F. Hiller von Gärtrin-gen). Berlin, 1913. IGBulg: Inscriptiones Graecae in Bulgaria repertae (ed. G. Mihailov) (1958-1970, 1997). 5 vols. Sofia. IK Heraclea Pont.: Jonnes, L. (1994). The Inscriptions of Heraclea Pontica. With a Prosopographia Heracleotica by Walter Ameling. Inschriften griechischer Städte aus Kleinasien, 47. Bonn. IK Sinope: French, D. H. (2004). The Inscriptions of Sinope. Inschriften griechischer Städte aus Klein-asien, 64. Bonn. Kerschner, M. (2005). Die Ionier und ihr Verhältnis zu den Phrygern und Lydern. Beobachtungen zur archäologischen Evidenz. – In: Neue Forschungen zu Ionien. Fahri Işık zum 60. Geburtstag gewidmet (eds. E. Schwertheim, E. Winter). Bonn, 113-146. LGPN: Lexicon of Greek Personal Names. (eds. P. M. Fraser, E. Matthews, et al.). Vol. I–V. Oxford, 1987–2018. Lenfant, D. (ed.) (2022). Grecs et non-Grecs de l’empire perse au monde hellénistique (Ktèma, no 47). Lewis, D. (2011). Near Eastern Slaves in Classical Attica and the Slave Trade with Persian Territories. – Classical Quarterly, New Series, No. 61/1, 91-113. MAMA VI: Buckler, W. H., Calder, W. M. (1939). Monuments and Documents from Phrygia and Caria. Monumenta Asiae Minoris Antiqua 6. Manchester. Masson, O. (1995). Les noms Daos et Azaretos en Mysie et en Bithynie. – In: Studia in honorem Georgii Mihailov (eds. A. Fol, B. Bogdanov, P. Dimitrov, D. Bojadžiev). Sofia, 325-328. Milet I.3: Kawerau, G., Rehm, A. (1914). Das Delphinion in Milet, Milet 1.3. Berlin. Milet VI.2: Herrmann, P. (1998). Inschriften von Milet. Teil 2, Inschriften n. 407-1019. Milet. Ergebnisse der Ausgrabungen und Untersuchungen seit dem Jahre 1899, VI, 2. Berlin, New York. Ramsey, W. M. (1883). The Cities and Bishoprics of Phrygia. – The Journal of Hellenic Studies, Vol. 4, 370-436. Robert, L. (1973). Sur les inscriptions de Délos. – Bulletin de correspondance helléniques, Supplément 1, 435-489. Rumschied, F. (ed.) (2009). Die Karer und die Anderen. Internationales Kolloquium an der Freien Universität Berlin, 13. bis 15. October 2005. Bonn. SEG: Supplementum epigraphicum Graecum, Leiden, 1923–. Sittig, E. (1911). De Graecorum nominibus theophoris. Halle. Snodgrass, A. M. (1964). Carian Armourers – The Growth of a Tradition. – The Journal of Hellenic Studies, No. 84, 107-118. van Bremen, R., Carbon, J.-M. (eds.) (2010). Hellenistic Karia. Proceedings of the First Conference on Hellenistic Karia, Oxford, 29 June - 2 July 2006. (Ausonius Éditions: Études 28). Bordeaux. Zgusta, L. (1964). Kleinasiatische Personennamen. Prag: Verlag der Tschechoslowakischen Akademie der Wissenschaften.